From Brain Gym Exercises to Classical Music - Suzić, Nenad; Janković, Tanja Stanković-; -Babić, Ozrenka Bjelobrk (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Conducted on the sample of 94 students aged 11 to 13, which were divided into the experimental (E) group and the control (C) group, each with 47 participating students, the present paper sought to evaluate an experimental program of music listening among elementary school children. Both groups were evenly balanced according to the following criteria: (1) number of pupils, (2) active enjoyment in music, (3) cognitive animation of music, (4) the expression of emotions toward music, (5) creativity in music, (6) general enjoyment in music, (7) preference to neo-folk music; (8) cognitive, (9) emotional, and (10) social involvement in classroom activities. The posttest results for the experimental group exhibited an incresed sgift in preference towards listening to and enjoyment in classical music. The experimental design included ten Brain Gym exercises. First, the participating students did two exercises while listening to folk songs they were familiar with. They performed simple conducting movements in the form of Lazy Eights, first for the folk song „I am a little gypsy girl“, and then the same for an aria from Carmen. The same pattern was used for the music piece titled „Rain“, and the marching beat.